5D Printing : A future beyond the scope of 4D printing with application of smart materials. Issue 1 (2nd January 2022) - Singh, Rishabh; Holmukhe, Rajesh M.; Gandhar, Abhishek; Kumawat, Karan
Abstract: The aim of the study is to present the technique currently used in 3D and 4D printing and add a 5D Printing dimension in the existing printing technique. This study illustrates the ways in which the fifth dimension could be implemented in present printing techniques in various fields. The methodology of study was a combination of review of research articles in 3D printing process, discussion with experts in 3D printing industry, field study to see the industrial applications of 3D printers, investigation of various materials used for 3D printing and documenting the various make-believe ideas of authors which can be implemented. The result of this investigation unearths some materials which have the ability to change shape during printing process, where the shape of an object changes when exposed to different environments. These materials can be termed as smart materials. These materials have helped in the evolution of 4D Printers. The industrial applications of 4D printing make clear that the needs of the future can be catered by the 4D Printed objects by utilizing smart and intelligent materials. The study concludes explaining that morphing is the main characteristics added to a 3D printed object giving rise to 4D printers and further if these shape changing characteristics of 4D printed objects can be controlled either by some sensors or actuators, then it can give rise to 5D printers.